Bypass of DNA-Protein Cross-links Conjugated to the 7-Deazaguanine Position of DNA by Translesion Synthesis Polymerases - Wickramaratne, Susith (J Biol Chem, 2016)
DNA-protein cross-links (DPCs) are bulky DNA lesions that form both endogenously and following exposure to bis-electrophiles such as common antitumor agents. The structural and biological consequences of DPCs have not been fully elucidated due to the complexity of these adducts. The most common site of DPC formation in DNA following treatment with bis-electrophiles such as nitrogen mustards and cisplatin is the N7 position of guanine, but the resulting conjugates are hydrolytically labile and thus are not suitable for structural and biological studies. In this report, hydrolytically stable structural mimics of N7-guanine-conjugated DPCs were generated by reductive amination reactions between the Lys and Arg side chains of proteins/peptides and aldehyde groups linked to 7-deazaguanine residues in DNA. These model DPCs were subjected to in vitro replication in the presence of human translesion synthesis DNA polymerases. DPCs containing full-length proteins (11–28 kDa) or a 23-mer peptide blocked human polymerases η and κ. DPC conjugates to a 10-mer peptide were bypassed with nucleotide insertion efficiency 50–100-fold lower than for native G. Both human polymerase (hPol) κ and hPol η inserted the correct base (C) opposite the 10-mer peptide cross-link, although small amounts of T were added by hPol η. Molecular dynamics simulation of an hPol κ ternary complex containing a template-primer DNA with dCTP opposite the 10-mer peptide DPC revealed that this bulky lesion can be accommodated in the polymerase active site by aligning with the major groove of the adducted DNA within the ternary complex of polymerase and dCTP.